Autophagy-mediated degradation of nuclear envelope proteins during oncogene-induced senescence - Lenain, Christelle; Gusyatiner, Olga; Douma, Sirith; van den Broek, Bram; Peeper, Daniel S (Carcinogenesis (New York), 2015)
Cellular senescence is a largely irreversible form of cell cycle arrest triggered by various types of damage and stress, including oncogene expression (termed oncogene-induced senescence or OIS). We and others have previously demonstrated that OIS occurs in human benign lesions, acting as a potent tumor suppressor mechanism. Numerous phenotypic changes occur during OIS, both in the cytoplasm and in the nucleus. These include the activation of autophagy, a catabolic process operating in the cytoplasm and downregulation of lamin B1, a component of the nuclear lamina. However, it is unknown whether these changes relate to each other. We discovered that cells entering BRAF(V600E)- or H-RAS(G12V)-induced senescence downregulate not only lamin B1 but also lamin A, as well as several other nuclear envelope (NE) proteins, resulting in an altered NE morphology. Depletion of LMNB1 or LMNA/C was sufficient to recapitulate some OIS features, including cell cycle exit and downregulation of NE proteins. We further found that the global loss of NE proteins is a consequence of their degradation by the autophagy machinery, which occurs concomitantly with autophagy induction and increased lysosomal content and activity. Our study therefore reveals a previously unknown connection between autophagy and the disruption of NE integrity during OIS.